Temperature and excipient mediated modulation of monoclonal antibody interactions revealed by kD, rheology, and Raman spectroscopy - Olivia Noelle Eskens; Sabitoj Singh Virk; Akashdeep Singh Virk; Deepika Venkataramani; Maureen Crames; Maria Calderon Vaca; Matthew Matusewicz; Connor Smith; Joshin George; Collin Taylor; Michael S. Marlow; Samiul Amin (mAbs, 2025)
High-concentration monoclonal antibody (mAb) formulations are frequently constrained by elevated viscosity and colloidal instability, stemming from enhanced intermolecular interactions under crowded conditions. In this study, we delineate the thermodynamic and rheological consequences of modulating protein-protein interactions through excipient-mediated and temperature-dependent mechanisms. Using an orthogonal analytical framework comprising diffusion interaction parameter (kD) measurements, high-shear rheometry, and Raman spectroscopic profiling, we interrogated mAb solutions at ~ 80 and 160 mg/mL across a physiologically and industrially relevant thermal window (5–45 °C). In the absence of ionic additives, high kD values (~60 mL/g) indicated dominant long-range electrostatic repulsions, resulting in suppressed self-association and lower viscosity. Incorporation of NaCl (0.05% w/v) markedly decreased kD (~16–20 mL/g), consistent with Debye screening of surface charges and a shift toward short-range hydrophobic and van der Waals attractions, which became especially pronounced at elevated protein concentrations and lower temperatures. Polysorbate 20 (0.05% v/v) mitigated these interactions via preferential surface adsorption, while sucrose exhibited a dualistic, concentration-dependent influence on viscosity via preferential exclusion and entropic crowding. The combination of NaCl and PS20 yielded the most pronounced rheological suppression, reflecting synergistic attenuation of both long-range repulsion and short-range association. Raman spectral analysis of Amide I/III regions confirmed structural invariance under thermal and shear stress, attributing viscosity modulation to colloidal rather than conformational perturbations. Collectively, these data elucidate the multivariate control of interparticle potentials in mAb solutions and provide a predictive basis for engineering subcutaneous formulations that optimize manufacturability, physical stability, and injectability through strategic manipulation of colloidal interaction landscapes.